1954
DOI: 10.1113/jphysiol.1954.sp005177
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the blood vessels of the human forearm to increases in transmural pressure

Abstract: Bayliss showed in 1902 that a sudden rise of arterial pressure causes the volume of the hindlimb of dogs, cats and rabbits to decrease below the original after a preliminary increase. The response was unaltered by acute denervation. He also found that arrest of the circulation to a curarized hindlimb for as little as 2 sec was followed by a large increase in the volume of the limb. These effects he ascribed to a direct reaction on the part of the muscular walls of the arteries, an increase in pressure causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
1
1

Year Published

1969
1969
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 8 publications
8
80
1
1
Order By: Relevance
“…80 There has been growing evidence to support this. Blair et al 81 documented that sub-atmospheric pressure induces an initial increase in arterial inflow in the forearm of healthy volunteers; Greenfield and Paterson 82 further showed a vasodilation effect on the arteries of the forearm in volunteers exposed to a subatmospheric pressure of À150 to À200 mm Hg, which is similar to the pressure used in VED. 14 Diederichs et al 83 noticed that negative pressure induces expansion of penile tissue followed by increase in blood flow in primates; the authors believed that the increased blood flow was arterial inflow.…”
Section: 48-52mentioning
confidence: 69%
“…80 There has been growing evidence to support this. Blair et al 81 documented that sub-atmospheric pressure induces an initial increase in arterial inflow in the forearm of healthy volunteers; Greenfield and Paterson 82 further showed a vasodilation effect on the arteries of the forearm in volunteers exposed to a subatmospheric pressure of À150 to À200 mm Hg, which is similar to the pressure used in VED. 14 Diederichs et al 83 noticed that negative pressure induces expansion of penile tissue followed by increase in blood flow in primates; the authors believed that the increased blood flow was arterial inflow.…”
Section: 48-52mentioning
confidence: 69%
“…When responses were expressed as the percentage change in forearm blood flow (Figure 1) to correct for possible changes caused by extraneous factors such as altered level of arousal [16], the conclusion that The mean (± s.e. mean) baseline angiotensin II level was 7.88 ± 1.1 pg ml-' (normal range 5-35 pg ml-') which did not differ significantly from placebo 7.4 ± 1.7 pg ml-'.…”
Section: Resultsmentioning
confidence: 99%
“…This calculated ratio corrects for all systemic factors that affect the regulation of blood flow in both arms (e. g. changes in blood pressure, level of arousal, hormonal changes etc. ), and ensures that only the direct effects of locally infused substances on forearm blood flow are taken into account [18]. In an earlier study on diurnal variations of forearm macro and microeirculation, the FBF ratio was demonstrated to be stable during the day [19].…”
Section: Methodsmentioning
confidence: 99%